Generation and Regeneration of Thymic Epithelial Cells - Alawam, Abdullah S.; Anderson, Graham; Lucas, Beth (Frontiers in Immunology, 2020)
The thymus is unique in its ability to support the maturation of phenotypically and functionally distinct T cell sub-lineages. Through its combined production of MHC-restricted conventional CD4+ and CD8+, and Foxp3+ regulatory T cells, as well as non-conventional CD1d-restricted iNKT cells and invariant gamma delta T cells, the thymus represents an important orchestrator of immune system development and control. It is now clear that thymus function is largely determined by the availability of stromal microenvironments. These specialised areas emerge during thymus organogenesis and are maintained throughout life. They are formed from both epithelial and mesenchymal components, and collectively they support a stepwise programme of thymocyte development. Of these stromal cells, cortical and medullary thymic epithelial cells represent functional components of thymic microenvironments in both the cortex and medulla. Importantly, a key feature of thymus function is that levels of T cell production are not constant throughout life. Here, multiple physiological factors including aging, stress and pregnancy can have either short- or long-term detrimental impact on rates of thymus function. Here, we summarise our current understanding of the development and function of thymic epithelial cells, and relate this to strategies to protect and/or restore thymic epithelial cell function for therapeutic benefit.